Typology of rural public places. On examples from Eastern Poland - Soszyński, Dawid; Kamiński, Jan (Bulletin of Geography. Socio-economic Series, 2022)
The paper proposes a typology of rural public places currently functioning in the social life of villages that indicates how this system is distinct from the public space of cities or even suburban villages. The research was conducted using the method of interviews in 21 villages in eastern Poland. The result of the analyses is a typology that includes eight basic types of rural public places: Multifunctional village squares; Grocery surroundings; Other service facilities surroundings; Sacred sites; Village streets; Neighborhood space; Recreational places; Semi-natural places. Most of them are unintentionally created places. The research shows that multifunctional places – both central and typically recreational – are crucial for rural areas, while semi-natural places are the most characteristic. However, due to the specific character of the rural landscape and rural community, we did not find any basis for distinguishing a separate category including arranged greenery, representative places or club spaces.